1981
DOI: 10.1085/jgp.77.6.693
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the sodium permeability of the luminal border of toad bladder by intracellular sodium and calcium: role of sodium-calcium exchange in the basolateral membrane.

Abstract: Sodium movement across the luminal membrane of the toad bladder is the rate-limiting step for active transepitheliaI transport. Recent studies suggest that changes in intracellular sodium regulate the Na permeability of the luminal border, either directly or indirectly via increases in cell calcium induced by the high intracellular sodium. To test these proposals, we measured Na movement across the luminal membrane (the Na influx) and found that it is reduced when intracellular Na is increased by ouabain or by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 43 publications
1
61
1
Order By: Relevance
“…6). Calcium taken up by the BLMV on the basis of the inwardly directed Ca2' chemical potential was, in part, effluxed uphill in the presence of a Na' gradient (26). Relationship of the Na+/Ca2+ exchange activity to external Na' concentration.…”
Section: Resultsmentioning
confidence: 99%
“…6). Calcium taken up by the BLMV on the basis of the inwardly directed Ca2' chemical potential was, in part, effluxed uphill in the presence of a Na' gradient (26). Relationship of the Na+/Ca2+ exchange activity to external Na' concentration.…”
Section: Resultsmentioning
confidence: 99%
“…10). cAMP, ATP, and norepinephrine have been reported to induce a similar Cl Ϫ secretion profile in M-1 cells, and at least the ATP effect is mediated by an increase in [Ca 2ϩ ] i (9,10,32,51 Earlier studies in other models of the collecting duct demonstrated that elevation of [Ca 2ϩ ] i reduces ENaC activity, although at least one prior study was unable to confirm this effect in M-1 cells (7,26,34,40). The mechanism for the inhibitory effect on Na ϩ transport is unknown, but an attractive hypothesis is that elevated [Ca 2ϩ ] i targets the C2-containing form of Nedd4 -2 to the plasma membrane where it can interact with ENaC, leading to channel internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a role for Gi in the action of PGE2 was examined using pertussis toxin. Finally, the possible role of increased cell cyclic AMP was examined using exogenous 8 Frindt and Windhager suggested that calcium inhibits Na' entry through the apical amiloride-sensitive sodium channel (27). Their data argue against inhibition of JNa by a direct action of Ca"+ on the basolateral Na+/K+-ATPase because ionomycin-induced inhibition ofJNa was reversed by amphotencin.…”
Section: Discussionmentioning
confidence: 99%